Hubungan ASI Tidak Eklusif Tehadap Status Gizi pada Anak Batita di Puskesmas Wonogiri Kecamatan Kotabumi Selatan Kabupaten Lampung Utara - Andoko Andoko; Linaawati Novikasari; Ahmad Windu Pranajaya (Universitas Malahayati Lampung, 2022)
ABSTRACT THE RELATIONSHIP OF NON-EXCLUSIVE BREASTFEEDING AND NUTRITIONAL STATUS TODDLERS IN WONOGIRI HEALTH CENTRE SOUTH KOTABUMI OF NORTH LAMPUNG REGENCY YEAR 2020Background: Exclusive breastfeeding according to the World Health Organization (WHO) is to give only breast milk without giving other food and drinks to babies from birth to 6 months of age, except drugs and vitamins. The incidence of malnutrition and undernutrition in children under five in 2013 increased to 8.3% and 27.5% respectively and in 2015 rose again to 8.8% and 28%, respectively. According to UNICEF (United Nation Children's Fund) in 2011, of the 136.7 million babies born worldwide, only 32.6% were exclusively breastfed. Objective: To determine the relationship between non-exclusive breastfeeding and the nutritional status of toddlers at the Wonogiri Health Centre, Kotabumi Selatan District, North Lampung Regency in 2020.Research Methods: This research is quantitative with a cross sectional approach. The population in this study were all mothers with toddlers aged 6-36 months in the work area of the Wonogiri Health Centre, Kotabumi Selatan District, North Lampung Regency, totaling 386 samples. The data analysis used was univariate and bivariate analysis with Chi-square test.Results: Obtained from the results of the Chi-square test, with p-value = 0, 000 which means pα (0.05), it can be concluded that there is a relationship between Non-Exclusive Breastfeeding and Nutritional Status in Toddlers in the Wonogiri Health Centre Work Area. North Lampung Regency in 2020. Breastfeeding significantly affects nutritional status with an OR value of 2,800, meaning that respondents who do not give exclusive breastfeeding have 2,800 times the possibility of children being at risk of malnutrition when compared to respondents with exclusive breastfeeding.Conclusion: It is known that there is a relationship between non-exclusive breastfeeding and nutritional status in toddlers at the Wonogiri Health Centre, Kotabumi Selatan District, North Lampung Regency in 2020. Keywords: exclusive breastfeeding, nutritional status, toddler INTISARI: HUBUNGAN ASI TIDAK EKLUSIF TEHADAP STATUS GIZI PADA ANAK BATITA DI PUSKESMAS WONOGIRI KECAMATAN KOTABUMI SELATAN KABUPATEN LAMPUNG UTARA Latar Belakang: ASI eksklusif menurut World Health Organization (WHO) adalah memberikan hanya ASI saja tanpa memberikan makanan dan minuman lain kepada bayi sejak lahir sampai berumur 6 bulan, kecuali obat dan vitamin. Kejadian gizi buruk dan gizi kurang pada balita pada tahun 2013 masing-masing meningkat menjadi 8,3% dan 27,5% serta pada tahun 2015 naik lagi menjadi masing-masing 8,8% dan 28%. Menurut UNICEF (United Nation Childrens Fund) pada tahun 2011, dari 136.700.000 bayi yang dilahirkan di seluruh dunia hanya 32,6% yang mendapatkan ASI eksklusif.Tujuan: Mengetahui hubungan ASI tidak eksklusif terhadap status gizi pada anak batita di Puskesmas Wonogiri Kecamatan Kotabumi Selatan Kabupaten Lampung Utara tahun 2020.Metode Penelitian: Penelitian ini adalah kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua ibu yang mempunyai batita usia 6-36 bulan di wilayah kerja Puskesmas Wonogiri Kecamatan Kotabumi Selatan Kabupaten Lampung Utara yang berjumlah 386 sampel. Analisis data yang digunakan adalah analisis univariat dan bivariat dengan uji Chi-square.Hasil: Didapatkan dari hasil uji Chi-square, dengan nilai p-value = 0, 000 yang berarti pα (0,05), maka dapat disimpulkan bahwa ada hubungan Pemberian ASI Tidak Eksklusif dengan Status Gizi pada Batita di Wilayah Kerja Puskesmas Wonogiri Kabupaten Lampung Utara tahun 2020. Pemberian ASI secara signifikan mempengaruhi status gizi dengan nilai OR 2,800 artinya responden yang tidak memberikan ASI eksklusif memiliki kemungkinan anak beresiko gizi kurang sebanyak 2,800 kali jika dibandingkan dengan responden dengan ASI eksklusif.Kesimpulan: Diketahui bahwa ada hubungan ASI tidak Ekslusif dengan Status gizi pada anak batita di Puskesmas Wonogiri Kecamatan Kotabumi Selatan Kabupaten Lampung Utara Tahun 2020. Kata Kunci: ASI eksklusif, status gizi, batita